Penerapan Bahasa Jurnalistik dalam Penulisan Naskah Siaran Berita Sulteng Faktual di LPP TVRI Sulteng - Henatisya Henatisya; Achmad Herman; Andi Akifah (Kanal: Jurnal Ilmu Komunikasi, 2016)
This research was conducted to find how the application of journalistic language and editing process in writing the script broadcast news on Sulteng Faktual program in LPP TVRI Sulteng. The research method used descriptive by determining the criteria of the texts containing the language of journalism was characterized by several things such as, television news writers must have the element accuracy, brevity, clartiy, simplicity, and sincerity. The result of the research showed that the structure of the literary language on Sulteng Faktual program in LPP TVRI Sulteng was often deviated from the use of language, ranging from word selection, and sentence structure. Meanwhile, in terms of editing the news script, there was no special team or someone who was fully responsible in editing the news script and filter the news that would be on air.